EGOISM AS A WAY OUT OF EXISTENTIAL CRISIS FOR A PERSON IN DISABILITY SITUATION - N. A. Mrinskaya (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose of the article is to establish the role of egoism in the life of a person faced with a disability situation, as a moment of self-determination in an existential crisis. I set the task to evaluate the influence of egoism and find out its significance in the prospect of the person’s further existence in the conditions of disability using the philosophical anthropology based on the meta-anthropology principle. Theoretical basis. Based on the fact that the role of egoism is perceived by public opinion as a vice and entails the absorption by a person of the benefits intended for others, I find them inappropriate for a person in a situation of disability. Taking into account the concepts of ego of altruism and altruistic egoism, which partially justify the positive influence of egoism, are only a product of the symbiotic interaction of altruism and egoism. The combination of egoism with altruism cannot reveal the essence of the crisis for a person in a disability situation. In a situation of disability, a person cannot synthesize altruism, as part of the egoism symbiosis. Methodological system in the study of the positive role of egoism, the modern theory of meta-anthropology by Nazip Khamitov is used. The theory that divides the being of a person into various types (ordinary, ultimate, and being beyond the bounds) is able to most fully structure the concept of egoism in the being of a person who has disability. Originality. I made an attempt to prove the positive role of egoism in a situation related to the body transformation into new conditions. The analysis of evidence of the need for the egoism development, as a function capable of actualizing a person in the formed crisis circumstances is carried out. A theory about the need for egoism to get a person out of the existential crisis situation (ultimate being) in which he stays due to a disability situation was proposed. Conclusions. I show that taking care of oneself (egoism) is a balancing factor for a person, as opposing a fatally unfair situation in which a person has received disability. Rational egoism is able to bring a person out of ultimate being and allow him to transform into a new, changed reality.